Pelatihan Literasi Bahasa Arab Dasar dengan Metode Tamyiz Muyassar Bagi Santri Pondok Pesantren Khairul Hikmah Bone Bolango - Arsyad, Berti; Saleh, Sriwahyuningsih R.; Doni, Chaterina P.; Pakaya, Nurul Aini; Safii, Randi (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to improve basic Arabic literacy among students at the Khairul Hikmah Islamic Boarding School through the application of the Tamyiz Muyassar method.. The activity was implemented using a descriptive and action research approach during the training period, involving 25 students as the main participants. Evaluation of the program's effectiveness was conducted using pre-test and post-test instruments to measure improvements in Arabic literacy skills. The results of this program's service have an impact on increased motivation and student activeness, as well as changes in the teacher's learning approach to a more participatory and interactive direction. It can be concluded that the Tamyiz Muyassar method is effective and relevant for improving basic Arabic literacy in Islamic boarding schools with limited facilities. This service provides a practical contribution in the form of an adaptive and contextual Arabic language training model, and has the potential to be developed and replicated in other Islamic boarding schools with similar characteristics.